2008
DOI: 10.1213/ane.0b013e318182aedb
|View full text |Cite
|
Sign up to set email alerts
|

Is a New Paradigm Needed to Explain How Inhaled Anesthetics Produce Immobility?

Abstract: A paradox arises from present information concerning the mechanism(s) by which inhaled anesthetics produce immobility in the face of noxious stimulation. Several findings, such as additivity, suggest a common site at which inhaled anesthetics act to produce immobility. However, two decades of focused investigation have not identified a ligand- or voltage-gated channel that alone is sufficient to mediate immobility. Indeed, most putative targets provide minimal or no mediation. For example, opioid, 5-HT3, gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 230 publications
(224 reference statements)
3
80
0
1
Order By: Relevance
“…Although immobility results from anesthetic action in the spinal cord (Antognini and Schwartz, 1993;Rampil et al, 1993), and ␣2 is highly expressed in the dorsal horn of the spinal cord (Bohlhalter et al, 1996), this negative result is consistent with the conclusions of previous studies with GABA A -R mutant mice and pharmacologic perturbations that GABA A -Rs have at most a limited role in mediating inhaled anesthetic-induced immobility (Eger et al, 2008). Furthermore, immobility is caused by actions of inhaled anesthetics on the ventral horn of the spinal cord (Barter et al, 2008;Jinks et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Although immobility results from anesthetic action in the spinal cord (Antognini and Schwartz, 1993;Rampil et al, 1993), and ␣2 is highly expressed in the dorsal horn of the spinal cord (Bohlhalter et al, 1996), this negative result is consistent with the conclusions of previous studies with GABA A -R mutant mice and pharmacologic perturbations that GABA A -Rs have at most a limited role in mediating inhaled anesthetic-induced immobility (Eger et al, 2008). Furthermore, immobility is caused by actions of inhaled anesthetics on the ventral horn of the spinal cord (Barter et al, 2008;Jinks et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Glycine Receptors. Glycine receptors are the primary mediators of inhibitory neurotransmission in the spinal cord and peripheral nervous system, where they are likely to mediate immobilizing effects of anesthetics (Eger et al, 2008). They have also been shown to play important roles in the central nervous system, including addiction pathways (Dutertre et al, 2012); for instance, the alcohol use disorder therapeutic acamprosate was recently shown to interact with glycine receptors in the nucleus accumbens to reduce dopamine release and ethanol consumption (Chau et al, 2010).…”
Section: A Eukaryotic Inhibitory Channelsmentioning
confidence: 99%
“…An important contribution of the approach is the ability to rule out potential targets. For example, the a1 subunit of the glycine receptor was considered one of the most likely mediators of spinal immobility produced by inhaled anesthetics (Eger et al, 2008), but this was shown not to be the case through use of knock-in mice (Borghese et al, 2012). A different approach was taken for nicotinic receptors, where gain of function was engineered into specific receptor subunits in mice (Drenan and Lester, 2012).…”
Section: A Behavioral Pharmacology In Rodent Modelsmentioning
confidence: 99%
“…The mechanism of how VAs work and the biochemical pathway(s) involved, however, are still not fully understood. It is generally thought that their anesthetic effects occur through multiple pathways, 3,4 although there also appears to be some evidence that indicates that individual VAs may work via unique pathways. 4 It is believed that VAs act upon different anatomic and molecular targets, thus providing the various behavioral responses that make general anesthesia so useful.…”
Section: Introductionmentioning
confidence: 99%